2021
DOI: 10.3390/brainsci11040507
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Audiovisual Representation of Phonemes in Children with Developmental Language Disorder

Abstract: We examined whether children with developmental language disorder (DLD) differed from their peers with typical development (TD) in the degree to which they encode information about a talker’s mouth shape into long-term phonemic representations. Children watched a talker’s face and listened to rare changes from [i] to [u] or the reverse. In the neutral condition, the talker’s face had a closed mouth throughout. In the audiovisual violation condition, the mouth shape always matched the frequent vowel, even when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…The evaluation of various language domains is an integral part of studying language skills. In our collection of articles, we discovered research concentrated on investigating language abilities in a group identified with DLD [31,35,37,39]. In these articles, there was a great diversity as they focused on different language domains, notably syntax, semantics, and pragmatics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The evaluation of various language domains is an integral part of studying language skills. In our collection of articles, we discovered research concentrated on investigating language abilities in a group identified with DLD [31,35,37,39]. In these articles, there was a great diversity as they focused on different language domains, notably syntax, semantics, and pragmatics.…”
Section: Resultsmentioning
confidence: 99%
“…In these articles, there was a great diversity as they focused on different language domains, notably syntax, semantics, and pragmatics. For example, Kagnovich and colleagues [37] measured general linguistic aptitude and working memory and they found children with DLD had difficulties integrating visual information into long-term a-phonemic representations. However, it should be noted none of the selected studies addressed the study of phonology separately.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from children with developmental language disorder (DLD, a.k.a. specific language impairment or SLI) and their typically developing age-matched peers were described in an earlier publication from our laboratory (Kaganovich et al, 2021). To be able to compare outcomes in both groups, we made the design child-friendly and used it with both children and adults.…”
Section: Methodsmentioning
confidence: 99%